2021
DOI: 10.1186/s12888-021-03470-1
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and health-related quality of life in a heterogeneous psychiatric sample: conditional indirect effects of pain severity and interference

Abstract: Background Few studies have examined clinically relevant mechanisms that underlie the association between two important indices of recovery— depression severity and health-related quality of life (HRQOL) in psychiatric outpatients. This study aimed to explicate the roles of pain interference and pain severity as mediating and moderating mechanisms in the relationship between depressive symptoms and HRQOL. Methods Data from 290 outpatients diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that elevated depressive symptoms are associated with lower health-related quality of life. However, many of these studies have recruited adult ( 14 29 ), clinical ( 16 , 18 23 , 25 28 , 30 38 ), or community samples ( 14 , 15 , 24 , 29 , 39 , 40 ), with limited generalizability. Rarely studies have included children and adolescents from the general population ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that elevated depressive symptoms are associated with lower health-related quality of life. However, many of these studies have recruited adult ( 14 29 ), clinical ( 16 , 18 23 , 25 28 , 30 38 ), or community samples ( 14 , 15 , 24 , 29 , 39 , 40 ), with limited generalizability. Rarely studies have included children and adolescents from the general population ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hyperalgesia, allodynia, and spontaneous pain, NeuP is also accompanied by the manifestation of emotional disorders including anxiety and depression ( 1 , 5 ). Notably, emotional disbalance further exacerbates NeuP ( 6 , 7 ). Although NeuP has become a major worldwide public health concern ( 8 ), the mechanisms underlying its pathogenesis remain unclear, and thus its treatment remains challenging.…”
Section: Introductionmentioning
confidence: 99%